2012
DOI: 10.5402/2012/941587
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Entropy Generation in a Fluid with Internal Heat Generation between Two Rotating Cylinders Subjected to Convective Cooling at the Surface

Abstract: Entropy generation analysis of a steady fluid flow with internal heat generation between two rotating cylinders was presented. The surface of the inner cylinder was kept at constant temperature while the surface of the outer cylinder was exposed to convection cooling. Analytical expressions for velocity and temperature distributions within the fluid were obtained. The effects of velocity ratio, Biot number, Brinkman number and other dimensionless parameters on the temperature distribution and local and total e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Doing this would reduce pressure drop in fire-tube, which in turn minimizes entropy generation rate and hence irreversibility in the system. The result is in agreement with Assad and Oztop [24], where they reported that entropy generation rate decreases with increasing radius.…”
Section: Effects Of Fire-tube Diameter On Entropy Generationsupporting
confidence: 92%
“…Doing this would reduce pressure drop in fire-tube, which in turn minimizes entropy generation rate and hence irreversibility in the system. The result is in agreement with Assad and Oztop [24], where they reported that entropy generation rate decreases with increasing radius.…”
Section: Effects Of Fire-tube Diameter On Entropy Generationsupporting
confidence: 92%
“…Torabi and Aziz (2012) solved local and total entropy generation inside an asymmetrically cooled hollow cylinder. Local and total entropy generation in steady fluid flow with internal heat generation between two rotating cylinders were also investigated for different velocity ratios, Biot number, Brinkman number by Haj Assad and Oztop (2012). Authors found that as the Biot number increases and Brinkman number decreases, the internal heat generation leads to minimum total entropy generation rate.…”
Section: Introductionmentioning
confidence: 99%
“…He used the concept of entropy to study these irreversible changes. Later, this concept was used by different researchers to examine the inherent irreversibility effects in different geometrical configurations [3][4][5][6][7][8][9][10][11]. However, less attention is being paid to the study of entropy effects on boundary layer flow and heat transfer processes over a stretchable surface.…”
Section: Introductionmentioning
confidence: 99%